Distribution, seasonal characteristics, ecological risks and human health risks of 9 antibiotics in the main water environment of Anhui province, China - Tang, Jie; Han, Yalin; Zha, Yan; Li, Xuede (Frontiers in Environmental Science, 2024)
This study was performed to determine the status and ecological risk as well as provide a basis for the prevention and control of antibiotic contamination in the drinking water sources of Anhui Province. Ultra Performance Liquid Chromatography (UPLC-MS/MS) was used to measure the detection rate and concentrations of nine antibiotics, classified as sulfonamides (SAs) or tetracyclines (TCs), in water collected from 51 sampling points and from areas with different seasonal characteristics. The risks of the main antibiotics (Sulfamethoxazole (SMZ), Doxycycline (DOC), Sulfadiazine (SDZ), Sulfamerazine (SM2), Sulfadimethoxine (SDM), Doxycycline (DOC), Tetracycline (TC), Oxytetracyline (OTC), and Chlortetracycline (CTC). to the ecosystem and human beings were evaluated using risk quotients (RQs) and target hazard quotients (THQs), respectively. Nine antibiotics were detected in tap water and surface water at concentrations ranging from 1.71 ng L−1–21.92 ng L−1 and 1.54 ng L−1–78.74 ng L−1, respectively. SMZ and DOC were detected in both tap water and surface water. Their highest detection rates in tap water were 59.1% and 63.6%, respectively, and those in surface water were 81.25% and 43.8%, respectively. SDZ, SMZ, SM2, SDM, DOC, TC, OTC, and CTC were detected in the dry and flood seasons, with levels ranging from 2.43 ng L−1–49.43 ng L−1. Among the detected target antibiotics, SMZ, SM2, TC, OTC, and CTC had higher detection rates. The total concentrations of detected antibiotics were higher in fall than in the other seasons. TC and OTC present in different water sources posed a moderate risk. SDZ present in surface water posed a higher ecological risk than that present in tap water and ground water. Meanwhile, the presence of DOC in tap water and the low risk caused by SDM in surface waters should be emphasized.